2-Hydroxy-4-n-butoxy-5-bromo propiophenone Thiosemicarbazone as Spectrophotometric Reagent for Iron - Parikh, K.S.; Patel, R.M.; Patel, K.N. (Asian Journal of Chemistry, 2010)
A simple, sensitive and specific spectrophotometric method has been developed for the determination of iron(II) in benzene. The metal ion reacts with 2-hydroxy-4-n-butoxy-5-bromo propiophenone thiosemicarbazone (HBBrPT) forming a dark red coloured complex in the pH range 5.0-9.0. The complex shows maximum absorption at 470 nm. Beer's law is obeyed in the range 13.96 μg/mL. The molar absorptivity and Sandell's sensitivity are found to be 2845 L mol-1 cm-1 and 0.01962 μg cm-2, respectively. The solid complex have been isolated and characterized on the basis of elemental analysis, UV, IR, NMR and mass spectra. 2-Hydroxy-4-nbutoxy- 5-bromo propiophenone thiosemicarbazone is found to be a selective and strong chelating agent for iron. The results deduced from Job's method of continuous variation, the mole ratio and the slope ratio method showed that metal: ligand ratio in the complex to be 1:2. The stability constant of the complex found to be 1.22 × 107. The free energy change for the complex formation reaction is found to be -9.989 K cal/mol at 35 ºC. The complex is fairly stable for about 24 h and up to 55 ºC.